Advanced Sustainable Epoxy Composites from Biogenic Fillers: Mechanical and Thermal Characterization of Seashell-Reinforced Composites - Kistak, Celal; Yanen, Cenk; Aydogmus, Ercan (Mdpi, 2025)
Featured Application Seashell-reinforced bio-based epoxy composites show enhanced thermal conductivity, hardness, and density, optimized via response surface methodology. FT-IR and microscopy confirm seashell powder as a chemically inert bio-filler. This scalable approach valorizes tidal seashell waste, supporting circular economy goals and enabling sustainable, lightweight materials for construction, marine, and automotive applications.Abstract Tidal seashell waste represents an abundant, underutilized marine resource that poses environmental disposal challenges but offers potential as a sustainable bio-filler in epoxy composites. This study investigates its incorporation into bio-based epoxy systems to reduce reliance on non-renewable materials and promote circular economy objectives. Processed seashell powder was blended into epoxy formulations, and response surface methodology was applied to optimize filler loading and resin composition. Comprehensive characterization included tensile strength, impact resistance, hardness, density, and thermal conductivity testing, along with microscopy analysis to evaluate filler dispersion and interfacial bonding. The optimized composites demonstrated improved hardness, density, and thermal stability while maintaining acceptable tensile and impact strength. Microscopy confirmed uniform filler distribution at optimal loadings but revealed agglomeration and void formation at higher contents, which can reduce interfacial bonding efficiency. These findings highlight the feasibility of valorizing marine waste as a reinforcing filler in sustainable composite production, supporting environmental goals and offering a scalable approach for the development of durable, lightweight materials suitable for structural, coating, and industrial applications.
Keywords: seashell powder; advanced bio-composites; sustainable materials; response surface methodology